1383 Welders for welders. (24th April 2018) - Nicholas, R; Danielsen, T; Mittal, A; Seneviratne, M; Naik, I
Abstract : Introduction: This program will create a means for welders who are already well-supported and protected in the formal sector, to help welders who are unsupported in the informal sector. Simply, well-protected welders would be able to donate small or large funds and new or used equipment to support the health and safety of unprotected welders. Methods: The primary tool for this program is triage—starting where we are with what we have. The program would bring together safety experts to translate knowledge and culture by listening, asking questions, and advising welders. Then, a form of triage could be developed for each situation, adapting the hierarchy of controls to the available resources and the work culture. In order for this program to succeed, it is essential that the formality of the organisation function well, but not interfere with the person-to-person relationships that are the foundation of this program. Results: The initial program will intentionally start small to allow flexibility and self-evaluation. Based upon the program's experiences, successes, and failures, financial and cultural demands, and the available resources, triage guidelines would be created and shared, defining welder protections from minimal to secondary to ideal. Through the program, others could be trained to make on-site visits, observe existing conditions, and then make and implement recommendations. A case study of welders in India will be provided to illustrate this concept. Conclusions: Ultimately, a health and safety triage template can be developed and made available for others to adapt to their own needs. In the future, 'Welders for Welders' could be applied to other skills in a broader context, perhaps with the creation of 'Workers for Workers.' By bridging two work environments, the proposed Welders for Welders program has the opportunity to promote a community of workers, with welders helping welders.